A NEW NATION ON THE BALTIC SEA? KASHUBIAN NOVELS BY ARTUR JABŁOŃSKI - Kalinowski, Daniel (Porównania, 2014)
The article includes a description of the ideological and artistic contents of two novels Namerkôny (2012) and Smùgã (2014) by Artur Jabłoński. The author of this literature is a historian, journalist, local politician, the former president of Kashubian-Pomeranian Association and the co-founder of Stowarzyszenie Osób Narodowości Kaszubskiej „Kaszëbskô Jednota” (The Association of Kashubian People „Kaszëbskô Jednota”). His novels make specific, ethnic interpretation of the history and the present of the Kashubians. In the first novel, the title protagonist is a stigmatized man who is rebellious and inquisitive. He seeks the Kashubian identity, which will be free of Polish and German political aims. The second novel in partial distance only declared in the title describes the contemporary reality of Pomerania from afar. This reality is full of materialism and consumerism whereas the unique individuals must somehow struggle with the hostile world. In both cases, the novel’s main character is subject to changes in their personality which lead them to become nationality-wise aware Kashubian men. The differences in plot and style between the novels stem from the fact that this development is carried out in the style of political fiction and social utopia (Namerkôny) or in the criminal or drama convention (Smùgã).